2016
DOI: 10.1158/0008-5472.can-14-3558
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxamic Acid and Benzoic Acid–Based STAT3 Inhibitors Suppress Human Glioma and Breast Cancer Phenotypes In Vitro and In Vivo

Abstract: STAT3 offers an attractive target for cancer therapy but small molecule inhibitors with appealing pharmacologic properties have been elusive. Here we report hydroxamic acid-based and benzoic acid-based inhibitors (SH5-07 and SH4-54, respectively) with robust bioactivity. Both inhibitors blocked STAT3 DNA binding activity in vitro and in human glioma, breast, and prostate cancer cells and in v-Src-transformed murine fibroblasts. STAT3-dependent gene transcription was blocked along with Bcl-2, Bcl-xL, Mcl-1, Cyc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 44 publications
3
92
0
Order By: Relevance
“…In addition, to examine selectivity, AM-1-124 was also assessed in a STAT1 [22] FP assay. FP experiments revealed that AM-1-124 was able to selectively disrupt a STAT3:IL-6R/gp130 peptide complex (Ki = 15.3 μM, Figure 3A) over that of the homologous STAT1:IFN-γ receptor complex (Ki > 250 μM, Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, to examine selectivity, AM-1-124 was also assessed in a STAT1 [22] FP assay. FP experiments revealed that AM-1-124 was able to selectively disrupt a STAT3:IL-6R/gp130 peptide complex (Ki = 15.3 μM, Figure 3A) over that of the homologous STAT1:IFN-γ receptor complex (Ki > 250 μM, Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Since STAT3 activity has been modulated by targeting pSTAT3-Y705 (pharmacological inhibitors, blocking antibodies, and dominant negative proteins) or total STAT3 protein accumulation (RNAi) or STAT3 dimers formation or binding to DNA (decoy oligonucleotides), the role of pSTAT3-S727 remained misunderstood in the cell fate control by STAT3. Interestingly, inhibiting STAT3 dimer formation and DNA-binding by the mean of STA-21, S3I-201 [83], hydroxamic acid-based (SH5-07) and benzoic acid-based inhibitors (SH4-54) [172] STAT3 inhibitors which target the STAT3 SH2 domain resulted in apoptosis or decreased cell proliferation (assessed by low BrdU incorporation). This depended on the state of cell differentiation, on the cell culture conditions and on the profile of STAT3 phosphorylation (pSTAT3-Y705 or pSTAT3-S727).…”
Section: Stat3 Function In Cell Survival and Proliferationmentioning
confidence: 99%
“…Inhibiting GR alone is not effective; basal-like cell lines proliferate and express some components of the basal-like gene signature without glucocorticoids in their media. Inhibiting STAT3 alone is not completely effective; previous studies have shown that SH4-54 killed basal-like cell lines in culture, but was insufficient to completely stop tumor growth in vivo where glucocorticoids are naturally present (24). These results indicate that inhibiting either of these TFs alone is not sufficient to abrogate the pro-proliferative gene expression program of basal-like breast cancer in vivo, but this study suggests that inhibiting both GR and STAT3 could be a novel and effective therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these TFs regulate important pathways in basal-like breast cancer and these TFs often regulate each other's expression (22,23). Several of these TFs can be inhibited with small molecule drugs and represent promising therapeutic targets (18,24,25). What remains unclear is which TFs are responsible for driving the gene expression signature that defines the basal-like TNBC subtype and which are downstream of the master regulator.…”
Section: Introductionmentioning
confidence: 99%